Structural Studies Of A Chemically Modified Thermostable Lipase From Geobacillus Sp. Strain T1 - Cheong, Kok Whye (2007)

(untitled)
Alkylation has been successfully performed using propionaldehyde on four batches of T1 thermostable lipase (M1, M2, M3 and M4) with different degrees of modification (27% to 55%) to represent the different levels of hydrophobicity. Based on the crystal structure, T1 possessed 11 lysine residues, of which four of the lysine residues, Lys84, 102, 138 and 251 have scores between 53.7% and 95.8% exposure ratio, were totally exposed. Another four residues, Lys185, 329, 344 and 345 have a ratio between 20% and 50% (moderately exposed) and three of the lysine residues, Lys28, 207 and 229 are buried. The hydrolytic activity of the modified enzymes dropped drastically by 10 to 40-fold upon chemical modification, despite both the native and modified form showed distinctive α-helical bands at 208 and 222 nm by Far Ultra-Violet Circular Dichroism (CD) spectropolarimetry. As cooperative unfolding transitions were observed, the modified lipases were distinguished from the native state, which the former possessed a Tm in lower temperature range, 60-64 ºC whilst the latter at 68 ºC. Consequently, this has led us to the hypothesis of formation of a molten globule (MG)-like structure. Subsequent analysis of both native and modified lipases by Matrix Assisted Laser Desorption/Ionization Time of Flight Mass Spectrometry (MALDI-TOF MS) study was carried out to ascertain the modifications and the location of these modifications. Four lysine residues, Lys28, 84, 207 and 329 were clearly identified from the native spectrum. As expected, Lys84 and Lys102 were clearly modified. Surprisingly, Lys185 which has a very low exposure ratio (27.5%) was also identified to be one of the modified residues. To further support the hypothesis of the formation of a molten globule, intrinsic and extrinsic fluorescence were performed. A decrease of fluorescence intensity was observed for modified lipase M1, which was modified using 0.5% of propionaldehyde. However, subsequent addition of propionaldehyde enhanced the fluorescence intensity of M2, M3 and M4, which indicated an inversion of placement for tryptophans to a more hydrophobic environment. As for extrinsic fluorescence, the alkylated lipases showed a clear enhancement of fluorescence intensity as compared to the native lipase due to the exposure of the hydrophobic interior of the enzymes.